PENGARUH BUDAYA ORGANISASI, KOMITMEN ORGANISASI DAN PENERAPAN PRINSIP-PRINSIP GOOD CORPORATE GOVERNANCE (GCG) TERHADAP KINERJA PERGURUAN TINGGI DENGAN PENDEKATAN BALANCED SCORECARD (BSC) - Fenty Astrina (Universitas Indo Global Mandiri)
The purpose of this research are to study and analyze the influence of organizational culture, organizational commitment and implementation good corporate governance principles towards university performance in Muhammadiyah University both simultaneously and partially. This research conducted at 7 faculties in Muhammadiyah University with amount of respondents are 223, from that amount there ara 82 declared complete for analysis. The data collecting was carried out by spreading questionnaires to lecturer and employee . The technical method of simple purpossive sampling. The tool of analyze is path analysis. The result on this research and hypothesis testing show that: (1) there is correlation among organizational culture and organizational commitment but not significant; (2) simultaneously, organizational culture, organizational commitment and good corporate governance had significant influence to university performance; (3) partially, organizational culture and organizational commitment had positive influence but not significant to university performance, good corporate governance had positive influence and significant to university performance.Managerial imlpication of the study is to focus more on increasing lecturer an employee commitment and socialize organization culture among lecturers and employees for increasing university performance.Keyword : Organization Culture, Organization Commitment, Good Corporate Governance, Organizational Performance.